On Collaboration: Adaptive and Multimodal Translation in Bilingual Inflight Magazines - Liu, Fung-Ming (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
There has been a proliferation in recent years of bilingual inflight magazines in the Greater China region, which indirectly serve the leisure industry, providing readers on and off airplanes with non-specialist information of an entertaining nature. This paper is a preliminary study of bilingual magazines published in Hong Kong, Mainland China and Taiwan, in which attention will be paid to: (a) the stages of production, (b) their translation strategies and (c) their modes of presentation. Two questions interest us most. First, what are the specific means whereby the effects of these multi-modal texts are achieved? The second question concerns the mechanics of operation in bilingual magazine publishing. This research will show the complex interaction of several parties as well as the blending of different modes of translating in the production of bilingual inflight magazines. Our findings should help researchers and practitioners in the field understand translation production in a different context from those to which they have been accustomed.